An ultralow concentration of Al-MOFs for turn-on fluorescence detection of aflatoxin B1 in tea samples. (30th July 2022) - Wang, Fuxiang; Li, Zuopeng; Jia, Hongping; Lu, Runhua; Zhang, Sanbing; Pan, Canping; Zhang, Zhiqiang
Highlights: Turn-on fluorescent sensing platform based on Al-metal organic frameworks was established for detection of aflatoxin B1 . An ultralow concentration of Al-metal organic frameworks was used at the sensor. The fluorescence detection system determined low concentration of aflatoxin B1 in real tea samples. The method design is simple, rapid, and had good sensitivity. Abstract: A turn-on fluorescent sensing platform based on an ultralow concentration of Al-metal organic frameworks for the detection of aflatoxin B1 has been developed for the first time. This fluorescence turn-on sensor exhibits the largest fluorescence enhancement (or quenching) constant value of 179404 M −1 among all luminescence-based chemical sensors reported till date. Moreover, the sensor afforded a rapid detection of aflatoxin B1, with a linear response in the concentration range of 0.05–9.61 μM and a low detection limit of 11.67 ppb. Additionally, the fabricated sensor showed good repeatability, reproducibility, stability, and selectivity. Most importantly, the practical application of this sensor has been demonstrated by detecting aflatoxin B1 in complex tea samples with low relative standard deviation (≤7.72%; n = 3) and satisfactory recoveries. In summary, the proposed method has great potential as a simple, sensitive and selective strategy for monitoring aflatoxin B1 in food samples.